Influence of cell wall polymers and their modifying enzymes during plant–aphid interactions. (12th December 2019) - Silva-Sanzana, Christian; Estevez, José M; Blanco-Herrera, Francisca
Abstract: Aphids are a major issue for commercial crops. These pests drain phloem nutrients and transmit 50% of the known insect-borne viral diseases. During aphid feeding, trophic structures called stylets advance toward the phloem intercellularly, disrupting cell wall polymers. It is thought that cell wall-modifying enzymes (CWMEs) present in aphid saliva facilitate stylet penetration through this intercellular polymer network. Additionally, different studies have demonstrated that host settling preference, feeding behavior, and colony performance of aphids are influenced by modulating the CWME expression levels in host plants. CWMEs have been described as critical defensive elements for plants, but also as a key virulence factor for plant pathogens. However, whether CWMEs are elements of the plant defense mechanisms or the aphid infestation process remains unclear. Therefore, in order to better consider the function of CWMEs and cell wall-derived damage-associated molecular patterns (DAMPs) during plant–aphid interactions, the present review integrates different hypotheses, perspectives, and experimental evidence in the field of plant–aphid interactions and discusses similarities to other well-characterized models such as the fungi–plant pathosystems from the host and the attacker perspectives. Abstract : This review highlights the different hypotheses, perspectives, and evidence that point to cell wall polymers and modifying enzymes as relevant plant traits for aphid resistance/susceptibility.